Implementasi Pariwisata terhadap Perekonomian Indonesia - Ahmad, Upi Sopiah (Al-DYAS, 2022)
Tourism plays an important role as a source of foreign exchange earnings and can contribute to the country's economic growth, can also reduce unemployment and increase productivity. Tourism is one of the strategic sectors for the development of an area in the context of national development. The ultimate goal of tourism development is to increase people's income, so as to create community welfare and economic growth, tourism development also increases and accelerates economic growth. Tourism activities create demand for consumption and investment which in turn leads to the production of goods and services. The impact of tourism on the Indonesian economy based on some literature shows that tourism has a very influential impact on the economy of a region, where by increasing the number of visitors to tourism it can increase existing tourism income and improve the welfare of tour owners, even creating jobs for someone who has not have a job, especially people who live in the tourism area. The existence of the tourism sector can have positive effects such as the development of tourism and the regional economy, the negative effect is more demand for tourism which will cause inflation. The tourism sector can develop the economy of a region and country, especially Indonesia which is rich in natural resources.